Innovation in a globalized world: Proximity-focused policy and border-crossing innovation projects. Issue 2 (26th July 2018) - Eklinder-Frick, Jens Ola; Perna, Andrea; Waluszewski, Alexandra
Abstract : Purpose: Previous IMP research has shown that innovation benefits tend to gravitate across organisational, company and legal borders. However, OECD and EU policy assume that innovation investments will create benefits in close spatial relation to where these were made. The overall purpose of this paper is to consider how opportunities and obstacles of innovation appear from the perspective of: a national policy actor, its regional mediators and a policy supported and research-based firm engaged in innovation. A specific interest is directed to what interactive aspects that are considered by these actors; in the using, producing and developing settings. Design/methodology/approach: Influenced by the research question and theoretical point of departure the authors investigate what type of interfaces our focal actors recognise in the using, producing and developing settings. A total of 41 face-to-face and phone interviews focusing on each actor's approach were conducted; 23 interviews in order to investigate the "policy side" of innovation attempts, while 18 interviews have been performed in order to understand a single business actor's innovation approach. Findings: The study shows that both the national policy agency and the regional policy mediators primarily operate within a developing setting, and furthermore, applies a rather peculiar interpretation of proximity. As long as the developing setting of the innovation journey is in focus, with the task to transfer academic knowledge advances to commercial actors, the proximity aspect is rather easy to fulfil. However, as soon as the producing and using settings of the innovation is taken into consideration, the innovation, if it survives, will gravitate to a producing setting where it can contribute to investments in place. Originality/value: The study investigates the opportunities and obstacles of innovation; the spatial aspects included, and how these are considered by: a national policy agency, a regional mediator and a policy-supported innovating firm, in order to juxtapose the policy doctrine with the experience of the business actors such policy wishes to support.